Profil dan Kinerja Usahatani Kangkung Darat (Ipomoea reptans) dalam Pola Diversifikasi dengan Padi Ciherang di Desa Abianbase, Kecamatan Mengwi, Kabupaten Badung - ARIMBAWA, I MADE PUTRA; WIDYANTARA, I WAYAN; DEWI, NI LUH PRIMA KEMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.1, Januari 2017, 2017)
Profile and Performance of Dry-Land Spinach (Ipomoea reptans) Farming InRice Ciherang Diversification Patten in Abianbase Village, Mengwi District,Badung Regency This study aimed to determine the profile of dry-land spinach farming and tocompare the dry-land spinach with rice ciherang views by income differences as wellas differences outpouring of labor in the family Village Abianbase. The researchmethod used was interview, observation, and direct documentation of 27 respondentsselected intentionally. The analysis used was descriptive analysis and comparisonanalysis. The results based on the characteristics of the respondent of swamp drylandspinach farmers seen from the age of more interest from group of productiveage and old age the average education level of famers dry-land spinach elementaryschool graduates, amount of children’s farmer an average had two late and secondjob as an average farmer laborers pelvis. Based on profit farming swamp dry-landspinach views of land area average used by 8 are, the total average cost of Rp.389.694,11/are with income Rp. 250.105,89/are and the value of R/C ratio of 1,64 orworth to developing. Based on comparative analysis of fevenue swamp dry-landspinach with rice which is the average income of dry-land spinachRp. 250.105,89/are and the average income of the rice is Rp. 147.956,63/are, whilebased a comparative analysis of the outpouring of labor in the family swamp drylandspinach amounting to 11,00 HOK/are and rice at 1,02 HOK/are.
Keywords: profile: performance: dry-land spinach: rice plant